![f(t)=6.5t^(-10)](https://img.qammunity.org/2023/formulas/mathematics/college/bpyt9ed4zrcwdfk3bqe9k7a189c3uh9v02.png)
then we have a new function:
![g(t)\text{ = }ln(6.5t^(-10)\text{)}](https://img.qammunity.org/2023/formulas/mathematics/college/3huva41bpcm2fkw1xsgiqab6hgdawh8h41.png)
its derivative is: the derivative of the outer function (natural logarithm) times the derivative of the inner function 6.5t^-10
that is:
![(dg(t))/(d(t))\text{ = }(1)/(6.5t^(-10))\frac{d}{d\text{ t}}\text{( }6.5t^(-10))^(\square)](https://img.qammunity.org/2023/formulas/mathematics/college/hpw7isfk715mopt9zkm4j6orjfz8h0273o.png)
the above because the derivative of the function ln is 1 / x , where in this case x = 6.5t^-10.
The above equation is equivalent to:
![(dg(t))/(d(t))\text{ = }(1)/(6.5t^(-10))\text{( -10 x}6.5t^(-11))^(\square)=\text{ }(1)/(6.5t^(-10))\text{( -}65t^(-11))=-10t^(-1)](https://img.qammunity.org/2023/formulas/mathematics/college/1v21fhq8hwm36k3181psnwtbgh77lovuvc.png)
So the correct answer is:
![(dg(t))/(d(t))\text{ = }(d)/(dt)\text{ }\ln (f(t))\text{= }-10t^(-1)](https://img.qammunity.org/2023/formulas/mathematics/college/9qqgx486eumnzr3aun88i57x3gy3qjve3v.png)